Penyuluhan Dan Pemeriksaan Mata Pada Siswa Sekolah Dasar Sebagai Upaya Menurunkan Angka Kebutaan Anak - Noviani Prasetyaningsih; Anggraeni Adiwardhani; Riani Witjaksana; Antin Tri Laksmi (CV. Multi Kreasi Media, 2024)
Refractive errors are one of the causes of blindness in the world. More than 2 billion people wear glasses worldwide and more than 60% have uncorrected refractive errors. Lack of parental knowledge about this disorder, excessive use of electronic devices such as smartphones, especially for playing games, is a trigger for the onset of refractive errors. Examination of children is somewhat difficult to do, so periodic screening is necessary. Objective: This Community Service Program aims to increase parents' knowledge of this disorder and the examination of refractive errors in school-age children. Methods: The implementation of the activity consisted of counseling to 62 parents of students and examination of refractive errors in 93 students in grades 4 and 5. Results: There was an increase in parents' knowledge about Refractive Errors and the dangers of excessive use of smartphone electronic devices. Refractive errors were found in 65.59% of students, of which 81.97% did not have glasses as a visual aid. We make free glasses for students in need.